Is There an Association between Socioeconomic Status and Body Mass Index among Adolescents in Mauritius? - Waqia Begum Fokeena; Rajesh Jeewon (The Scientific World Journal)
There are no documented studies on socioeconomic status (SES) and body mass index (BMI) among Mauritian adolescents. This study aimed to determine the relationships between SES and BMI among adolescents with focus on diet quality and physical activity (PA) as mediating factors. Mauritian school adolescents (𝑛=200; 96 males, 104 females) were recruited using multistage sampling. Participants completed a self-reported questionnaire. Height and weight were measured and used to calculate BMI (categorised into underweight, healthy-weight, overweight, obese). Chi-square test, Pearson correlation, and Independent samples 𝑡-test were used for statistical analysis. A negative association was found between SES and BMI (𝜒2=8.15%, 𝑃<0.05). Diet quality, time spent in PA at school (𝑃=0.000), but not total PA (𝑃=0.562), were significantly associated with high SES. Poor diet quality and less time spent in PA at school could explain BMI discrepancies between SES groups.